2017
DOI: 10.25081/jsa.2017.v1.825
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of micro and macro nutrients in poultry feeds available in Dhaka city, Bangladesh.

Abstract: This study was based on to determine the concentration of macro and micro nutrients as well as toxic and nontoxic heavy metals present in the chicken feed available in Dhaka city of Bangladesh. All macro nutrients, if present in the feed at high concentration have some adverse effect, at the same time if this nutrient present in the feed at low concentration this have some adverse effect too. So that this nutrient level should be maintained at a marginal level. On the other side toxic heavy metals if present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
2
3
1
Order By: Relevance
“…And these recorded limits were exceeded the permissible limits of WHO, (1992 &1995) (80 ppm) and FAO, (45-80mg/kg). The obtained results were in agreement with or slightly higher than those obtained by (Islam et al, 2017) in Dhaka city, Bangladesh that ranged from 57.3 to 121.9 mg/kg. The high levels of iron in feed can be attributed to the farmers and companies that manufacture poultry feed adding high amounts of iron in order to avoid deficiencies as it leads to severe anemia and loss of pigmentation, also decreased growth rates (Ma et al, 2014).…”
Section: Resultssupporting
confidence: 89%
“…And these recorded limits were exceeded the permissible limits of WHO, (1992 &1995) (80 ppm) and FAO, (45-80mg/kg). The obtained results were in agreement with or slightly higher than those obtained by (Islam et al, 2017) in Dhaka city, Bangladesh that ranged from 57.3 to 121.9 mg/kg. The high levels of iron in feed can be attributed to the farmers and companies that manufacture poultry feed adding high amounts of iron in order to avoid deficiencies as it leads to severe anemia and loss of pigmentation, also decreased growth rates (Ma et al, 2014).…”
Section: Resultssupporting
confidence: 89%
“…Diet is most likely the main source of Cd exposure in Bangladesh for those who live in rural environments with essentially no industrial contamination. The rice-based diet in the population contributes to 20–35 μg Cd daily 5,32,33. These studies highlight the fact that elevated Cd concentrations in rice is a widespread problem and the present study has identified, for the first time, which Bangladeshi populations are exposed to excessively high levels of Cd in their diet.…”
Section: Resultssupporting
confidence: 55%
“…Consequently, Cd consumption may cause chronic effects on the human body, such as cancer, kidney damage, and inhibit enzymatic activities. In Bangladesh, young children (1.5–5 years) are primarily exposed to Cd, especially in rural areas 5,46. Pregnant women are also particularly vulnerable to Cd exposure in Bangladesh 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations